A Comparative Study on the Effects of Functional and Non-Functional Fatigue Protocols on Dynamic Balance of Amateur Basketball Players - Sasan Naderi; Hamidreza Naserpour; Fariborz Mohammadi-Pour; Mohammadreza Amir-Seyfaddini (Islamic Azad University, Hamedan Branch, 2019)
Objective: The purpose of the present study was to compare the effects of functional and non-functional fatigue protocols on the dynamic balance of amateur basketball players. Methods: Ten amateur basketball players (mean age= 21.4±1.5 years, mean height= 177.5±7.1 cm, and mean weight= 67.4±8.5 kg) volunteered to participate in this study. Stair climbing and specific basketball movement circuit training were used to induce the non-functional and functional fatigues, respectively. Dynamic balance was measured by the postural stability test (level 2) using the Biodex balance system. Paired T-test and independent T-test were used for data analysis at a significance level of P<0.05. Results: Dynamic balance of subjects was decreased after inducing both fatigue protocols, where the non-functional fatigue protocol reduced the overall balance by 21.39%, and the functional protocol reduced it by 10.49%. There was a significant difference between the pre-test and post-test scores of overall balance and the balance in the anterior-posterior direction following the non-functional fatigue protocol (P=0.03). Conclusion: Non-functional fatigue protocol affects the dynamic balance of basketball players more than the functional protocol. Therefore, using different types of specialized exercises to experience the period of fatigue may be effective in improving the balance of basketball players.